HOUSING DESIGN WITH RAINWATER HARVESTING SYSTEM FOR HOUSING TYPE 36 AND TYPE 48 - Deo Demai Kopaba; Widya Fransiska; Edward Saleh (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Housing procurement for low to middle-income people in Palembang is carried out by the government and developers with the direction of housing development towards the outskirts of the city. One of the directions of development is the Talang Kepuh area, Ilir Barat 1 district. Housing development in this area is carried out in a wetland area where some of the condition of the area is swampland so that in its construction it must have its characteristics because the land has been piled up. In addition, the problem of housing development is the difficulty of the need for clean water. Simple housing design that is environmentally sound with rainwater harvesting system as an alternative solution to problems in water supply, so that it can meet the residential needs of the community. The results of the analysis discussion are outlined in the form of a simple concept of planning and designing a simple house with an environmental perspective. Rainwater harvesting is an important use to reduce excess surface runoff that causes flooding, land subsidence, and dryness of groundwater reserves. Where rainwater from the roof of the house will be dispensed into the distribution pipes which will then be forwarded and accommodated in water tanks. Meanwhile, if the excess water is accommodated, it will be dispensed to the retention pond. The calculation is done by calculating the discharge from the rainwater covering the roof of the house, then the volume of the water tank will be obtained to get the dimensions. After getting the dimensions of the water bath will be calculated the necessary costs. The costs calculated are excavation and backfill of soil, concrete materials, pipelines, and workers' wages. So that a water reservoir can be made with concrete material that will be used for water needs. The stored water will be used as raw water. For use as cooking or drinking water, further research is needed.